Antidepressant-like effect of extracts from Urtica dioica in mice model of depression - Amir Modarresi Chahardehi; Darah Ibrahim; Farid Abolhassani; Shaida Fariza Sulaiman (Syiah Kuala University, 2012)
Urtica dioica (Stinging nettle) leaves have been used as a traditional medicine to treatrheumatoid arthritis, to alleviate rheumatic pain benign prostatic hyperplasia (BPH), diuretic and prevention of kidney stones by local people in Middle East region especially in Iran, Turkey and East Europe. Hence, this investigation evaluates the antidepressant effect of selected crude extracts in the forced swimming test (FST) and tail suspension test (TST), two models predictive of antidepressant activity. The acute treatment of mice with extracts by intra-peritoneal (i.p.) route significantly reduced the immobility time in the FST (50 and 100 mg/kg) and TST (50 and 100 mg/kg), as compared to positive controls (haloperidol and fluoxetine) at 1 and 10 mg/kg, respectively. On the third day of experiment, a significant decrease of mobility was observed for chloroform extract (CE I) and butanol extract (BE II) compared to first day. CE I and BE II led to reduction of immobility time, as the selected extracts with two doses administered were different compared to the control, in the FST method by 65.37% and53.92% for 100 mg/kg, respectively. However, CE I showed the best result compared to our positive controls. Similar results of increased antidepressant effect, that was, of immobility time depending on the concentration administered, were obtained with the TST method. Also our data showed that there was no significant differences between doses (50 and 100 mg/kg). The results suggested that the antidepressant action of the butanol extract and of U. dioica its fraction (BE II2) was mediated by an interaction with 5-hydroxytrptamine (5-HT). U. dioica showed a potential source for the isolation of important natural products with antidepressant-like properties. However, further studies are still required